Cause‐Specific Mortality in Male US Veterans With Rheumatoid Arthritis. Issue 1 (January 2016) - England, Bryant R.; Sayles, Harlan; Michaud, Kaleb; Caplan, Liron; Davis, Lisa A.; Cannon, Grant W.; Sauer, Brian C.; Solow, Elizabeth B.; Reimold, Andreas M.; Kerr, Gail S.; Schwab, Pascale; Baker, Josh F.; et al.
Abstract : Objective: There has been limited investigation into cause‐specific mortality and the associated risk factors in men with rheumatoid arthritis (RA). We investigated all‐cause and cause‐specific mortality in men with RA, examining determinants of survival. Methods: Men from a longitudinal RA registry were followed from enrollment until death or through 2013. Vital status and cause of death were determined using the National Death Index. Crude mortality rates and standardized mortality ratios (SMRs) were calculated for all‐cause, cardiovascular disease (CVD), cancer, and respiratory mortality. Associations with all‐cause and cause‐specific mortality were examined using multivariable Cox proportional hazards and competing‐risks regression. Results: There were 1, 652 men with RA and 332 deaths. The leading causes of death were CVD (31.6%; SMR 1.77 [95% confidence interval (95% CI) 1.46–2.14]), cancer (22.9%; SMR 1.50 [95% CI 1.20–1.89]), and respiratory disease (15.1%; SMR 2.90 [95% CI 2.20–3.83]). Factors associated with all‐cause mortality included older age, white race, smoking, low body weight, comorbidity, disease activity, and prednisone use. Rheumatoid factor concentration and nodules were associated with CVD mortality. There were no associations of methotrexate or biologic agent use with all‐cause or cause‐specific mortality. Conclusion: Men in this RA cohort experienced increased all‐cause and cause‐specific mortality, with a 3‐fold risk of respiratory‐related deaths compared to age‐matched men in the general population. Further studies are needed in order to examine whether interventions targeting potentially modifiable correlates of mortality might lead to improved long‐term survival in men with RA.